An Analytical and literey study of the Quranic Commentary and the Interpretation of the Quran: https://doi.org/10.5281/zenodo.17702188 - Asima Qayyum; Anam Jamil; Dr Taswar Hussain (Journal of Religion and Society, 2025)
"The Holy Quran is the final divine and revolutionary book revealed by Allah Almighty. It was sent down to transform the lives of human beings. Without this sacred guidance, creation cannot truly recognize or understand its Creator." "The Holy Quran is a source of guidance for all human beings. It encompasses all matters related to human life, from birth to death. Moreover, the possibility of any distortion in it has been eliminated until the Day of Judgment." "The Holy Qur'an is a treasure trove of knowledge, from which scholars extract insights according to their individual capacities. Allah Almighty has revealed two primary types of verses within it. One category consists of clear commands and legal rulings. The other encompasses a broad range of themes, including monotheism (Tawheed), prophethood, exhortation and guidance, warnings and admonitions, narratives and parables, vivid depictions of the Day of Judgment, and detailed descriptions of Paradise and Hell. Each type serves a divine purpose, addressing the intellect, spirit, and moral compass of humanity." "Approximately five hundred verses in the Holy Qur'an pertain to legal rulings, the details of which have been thoroughly explained by jurists and commentators. Over the centuries, countless translations and interpretations of the Qur'an have been produced in various languages—an immense blessing for the Muslim Ummah. Allah Almighty has instilled such wisdom and flexibility in the rulings of the Qur'an and Sunnah that they continue to offer guidance for issues that arise up to the Day of Judgment. For this reason, the door of ijtihad (independent legal reasoning) has remained open, allowing qualified scholars to address new challenges in light of the foundational principles of Islam." This is why the door of ijtihad has been kept open until the Day of Judgment—to address emerging issues in light of the Qur'an and Sunnah. In the present era, the Muslim Ummah is confronted with numerous unprecedented challenges. However, some scholars tend toward exaggeration or deviation when engaging in ijtihad directly from the Qur'an and Sunnah without proper methodology. Recognizing this, the three selected commentators have addressed various jurisprudential issues in their respective interpretations, offering insights that are particularly relevant to contemporary life. This article presents a research-based, comparative analysis of these selected verses across these three interpretations, focusing on the legal rilings derived from them and their application to modern contexts . Keywords: Quranic Exegesis, Tafsir Studies, Literary Analysis, Interpretative Methodology, Quranic Hermeneutics